Analisis Kebijakan Kurikulum Merdeka Di Sekolah Dasar: Systematic Literature Review - Dian Margaretha; Masbirorotni Masbirorotni; Eddy Haryanto (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the concepts and policy directions of the Merdeka Curriculum at the elementary school level; identify opportunities it offers for the development of basic education; map out the challenges of its implementation; and formulate effective strategies to support its optimal implementation. The study employs a Systematic Literature Review approach. The findings indicate that the Merdeka Curriculum offers significant opportunities, including greater autonomy for teachers in designing instructional materials, strengthening the Pancasila Student Profile through project-based learning, and the application of a deep learning approach. However, its implementation faces substantial challenges, namely low levels of teacher readiness in terms of psychological preparedness, knowledge, and behavior; disparities in digital infrastructure, particularly in remote areas; uneven dissemination of the policy; and slow bureaucratic responses at the local government level. Overall, the study’s findings indicate that the success of the curriculum is not solely determined by regulatory design but depends on the alignment between consistent government policies, educator competencies, and a supportive educational ecosystem. Recommended strategies include intensive and sustained professional development for teachers, equitable infrastructure distribution in underdeveloped areas, and active and innovative leadership from school principals.